Significance and etymology of number ethnonyms in ancient Turkic written monuments - Nurilya Shaimerdinova, Zhadyra Aidarbekova,; Ardak Tleulesova, Aitbala Abdrakhmanova,; Begimova, Gulzhanat (Opción, 2019)
The purpose of the article is to determine the numerical ethnonyms of the ancient Turkic written monuments via lexical-semantic, etymological, ethnolinguistic, and linguocultural research methods. The article identified the nature and function of numerical ethnonyms of the Turkic written monuments in the culture of the Turkic peoples It also identified the general function of numerators in shaping the world image in the culture of the Turkic peoples. In conclusion, one can determine the structural basis, the sub-ethnic component of ethnic groups, by establishing historical, linguistic, cultural, and cognitive relations between numbers and ethnic groups.